Late Nonalcoholic Fatty Liver Disease with Cirrhosis: A Pathologic Case of Lost or Mistaken Identity - Lefkowitch, Jay H.; Morawski, John L. (Seminars in Liver Disease, 2012)
Late-stage nonalcoholic fatty liver disease (NAFLD) may present clinically and/or pathologically as cryptogenic cirrhosis. The subject of this report, a middle-aged obese man with diabetes, underwent liver biopsy at the time of laparoscopic cholecystectomy because the liver surface appeared nodular and thickened. The biopsy showed relatively nondescript cirrhosis at initial low-power microscopic inspection, but glycogenated hepatocyte nuclei (consistent with diabetes), sparse macrovesicular fat, and very rare foci of residual mild steatohepatitis were later found. Slender fibrous septa (without significant inflammation and often enclosing microvessels) were present and interconnected to portal tracts. Immunostains for cytokeratin 7, ubiquitin, and glutamine synthetase provided additional histologic data supporting NAFLD as the cause of the cirrhosis in this case. A strategic pathologic approach is discussed, which can be utilized for the pathologic assessment of cirrhosis of unknown cause, particularly when late NAFLD is suspected.
Keywords: Nonalcoholic fatty liver disease; nonalcoholic steatohepatitis; obesity; diabetes; cryptogenic cirrhosis; glutamine synthetase